ANALYSIS OF SUPPLEMENTARY FOOD PROVISION AND NUTRITIONAL COUNSELING THROUGH HEALTH PROGRAMS TARGETING NUTRITIONAL IMPROVEMENT IN TODDLER CHILDREN (A STUDY AT TAMANAN BONDOWOSO HEALTH CENTER) - Nia Damayanti; Toni Herlambang; Mohammad Thamrin (RADJA PUBLIKA, 2024)
The main issue related to malnutrition is parental knowledge. Education also affects parents' mindset regarding health issues. Higher education levels among parents influence their ability to correctly receive or understand information about maintaining their own health and that of their children, especially in providing adequate nutrition. Parents who are sensitive to education will strive to seek information to enhance their knowledge. Malnutrition issues generally occur in children of preschool age. This research was conducted at the Tamanan Health Center with the aim of testing and analyzing the influence of service quality and facilities on patient satisfaction, mediated by the competence of the staff. The research subjects were parents with preschool children participating in nutrition service programs at both the Tamanan Health Center and the integrated health posts (Posyandu) within the Tamanan Health Center's working area. The study was conducted from March to May 2025, involving 140 respondents. The results show that the provision of supplementary food has a positive and significant impact on the health program for preschool children at the Tamanan Health Center. Nutritional counseling has a positive effect but is not significant for the health program at the Tamanan Health Center. The provision of supplementary food positively impacts but is not significant for the nutritional improvement targets for preschool children at the Tamanan Health Center. Nutritional counseling positively and significantly affects the nutritional improvement targets for preschool children at the Tamanan Health Center in Bondowoso. The health program positively and significantly influences the nutritional improvement targets for preschool children at the Tamanan Health Center in Bondowoso. The provision of supplementary food has a positive and significant effect on nutritional improvement targets through the health program at the Tamanan Health Center in Bondowoso. Nutritional counseling has a positive effect but is not significant for the nutritional improvement targets through the health program at the Tamanan Health Center in Bondowoso.